Level of Adherence to the Dietary Recommendation and Glycemic Control Among Patients with Type 2 Diabetes Mellitus in Eastern Ethiopia: A Cross-Sectional Study - Mohammed AS (Dove Medical Press, 2020)
Ammas Siraj Mohammed,1 Fuad Adem,1 Yohannes Tadiwos,2 Nigist Alemayehu Woldekidan,3 Amsalu Degu4 1Department of Clinical Pharmacy, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2Department of Pharmacology, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Department of Clinical Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 4Department of Pharmaceutics and Pharmacy Practice, School of Pharmacy and Health Science, United States International University Africa, Nairobi, KenyaCorrespondence: Ammas Siraj Mohammed Email ammassiraj2337@gmail.comBackground: Dietary modification is the cornerstone and initial recommendation in the management of diabetes mellitus. Adhering to the recommended dietary practice has a significant role in diabetic control, but not uniformly practised.Objective: To assess dietary adherence and glycemic control among type 2 diabetic patients on follow-up at Dilchora Referral Hospital (DRH), Dire Dawa, Eastern Ethiopia.Methods: A hospital-based cross-sectional study was conducted from 22 August to 23 October 2019, at DRH. Data were collected through an interviewer-administered questionnaire. The Perceived Dietary Adherence Questionnaire (PDAQ) was used to estimate the level of dietary adherence. Glycemic control was measured using fasting blood glucose. Multivariate logistic regression analyses were employed to identify factors associated with dietary adherence.Results: Of the 307 included patients, 62.5% were poorly adherent to the recommended diet. Lack of dietary education (83.38%) and inability to afford a healthy diet (71.33%) were the perceived barriers to practice dietary recommendation. More than half (54.7%) failed to achieve the recommended fasting blood glucose target. In multivariate logistic regression, patients who were adherent to dietary recommendations were 3.56 times more likely to have good glycemic control. Those patients living in urban areas, having monthly income greater than 1000 Ethiopia Birr, family history of the disease, duration of treatment greater than 10 years and who received counseling were more likely to have good dietary adherence.Conclusion: The level of adherence to the dietary recommendation and glycemic control was low. Healthcare providers should be proactive in tackling the barrier for non-adherence and should promote adherence to dietary recommendations in T2DM patients.Keywords: type 2 diabetes, dietary adherence, glycemic control, Eastern Ethiopia